Beyond Functional Branding: An Interpretive Analysis of Human-Likeness, Transparency, and Brand Engagement in Multinational Companies - Aji, Alwis Fauzi Prio (Generate Digital Publishing, 2025)
Objective: This study aims to develop an interpretive understanding of how human-likeness and transparency in corporate brand communication jointly shape brand engagement within cross-cultural multinational contexts. Specifically, it examines how human-like communication and perceived transparency influence trust formation, emotional closeness, and consumer behavioral engagement across different cultural settings. Research Design & Methods: Adopting an interpretive qualitative research design, this study draws on in-depth semi-structured interviews with corporate communication managers from six multinational companies and consumers from five countries (the United States, Germany, Japan, South Korea, and Indonesia). The data were analyzed using reflexive thematic analysis to uncover recurring meaning structures that explain how human-likeness and transparency are interpreted and enacted across cultural contexts. Findings: The findings reveal that human-likeness functions as a relational mechanism that fosters emotional closeness through empathy, warmth, and personalized communication, while transparency operates as a culturally situated signal of integrity that builds trust through perceived consistency between corporate values and actions. Importantly, the study shows that authentic brand engagement emerges from the interaction between human-likeness and transparency, rather than from either dimension alone. This interaction manifests differently across collectivist and individualist cultures, shaping consumer participation, advocacy, and loyalty in distinct ways. Implications & Recommendations: The findings position human-likeness and transparency as interrelated dimensions of corporate humanization that enhance brand engagement beyond transactional approaches. For multinational companies, culturally adaptive human-like communication and responsible transparency are essential to building trust, reducing skepticism, and fostering ethically grounded corporate–consumer relationships. Contribution & Value Added: By offering an integrative conceptual framework that links human-likeness and transparency to authentic brand engagement in cross-cultural contexts, this research provides novel interpretive insights and enriches the literature on global branding, corporate humanization, and cross-cultural marketing communication.